1976
DOI: 10.1021/ja00423a050
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic hydration of [18O]epoxides. Role of nucleophilic mechanisms

Abstract: The hydration of five mono-and 1,1-disubstituted oxiranes by enzymes in rat liver microsomes has been shown, by means of ,sO-tracer studies, to be extremely regiospecific, involving cleavage of the C(2)-0 bond of the oxirane ring. Basecatalyzed hydration of these epoxides also involved C(2)-0 bond cleavage but was much less regiospecific, whereas acid-catalyzed hydration involved mainly C(l)-0 bond cleavage. Both the enzymatic and metal ion catalyzed hydration of [lgO]-2pyridyloxirane were found to involve >95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…Racemic styrene oxide (1S, 2S)-1-phenylpropylene oxide and (1R, 2R)-1-phenylpropylene oxide were purchased from Sigma-Aldrich (St. Louis, MO, USA), and used as standard products. Other standard products including racemic 1-phenylcyclohexene oxide and 2-(oxiran-2-yl)pyridine were synthesized from the corresponding alkenes according to the literatures (Fieser and Fieser, 1967;Hanzlik et al, 1976). Other reagents were purchased from general suppliers and were used without further purification.…”
Section: Chemicalsmentioning
confidence: 99%
“…Racemic styrene oxide (1S, 2S)-1-phenylpropylene oxide and (1R, 2R)-1-phenylpropylene oxide were purchased from Sigma-Aldrich (St. Louis, MO, USA), and used as standard products. Other standard products including racemic 1-phenylcyclohexene oxide and 2-(oxiran-2-yl)pyridine were synthesized from the corresponding alkenes according to the literatures (Fieser and Fieser, 1967;Hanzlik et al, 1976). Other reagents were purchased from general suppliers and were used without further purification.…”
Section: Chemicalsmentioning
confidence: 99%
“…Racemic and (S)-styrene oxides were purchased from SigmaAldrich. Racemic a-methylstyrene oxide and a-ethylstyrene oxide were synthesized by treating the corresponding olefins with N-bromosuccinimide, followed by the conversion of the bromohydrins to epoxides (Hanzlik et al 1976). Other reagents and substrates were obtained from general suppliers and were used without further purification.…”
Section: Chemicalsmentioning
confidence: 99%
“…The closest examples of methyl-substituted arene oxides that have been studied are 2,5-dimethylbenzene 1,2-oxide and 2-methylnaphthalene 1,2-oxide, but these were found not to be substrates of guinea pig liver microsomes (18). Recent studies on the hydration ofmonosubstituted and 1, 1-disubstituted oxirane ['80]oxides by rat liver microsomes indicated that epoxide hydrolase activates water molecules for nucleophilic attack at the less hindered oxirane carbon (19). Thus, based on the available evidence, mechanism ii is less likely to be responsible for the observed results presented in this paper.…”
Section: Resultsmentioning
confidence: 99%